The implications of honour and shame in Matthew 5:38-42 and in Unhu philosophy as a response to the political violence in Zimbabwe - Gusha, Tapiwa Huggins (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.